2014
DOI: 10.1007/s11920-014-0468-6
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Depression: An Update and Overview

Abstract: Over the last 3 years there have been notable developments in screening and treatment of perinatal depression. Most importantly, the DSM-V has made only minor changes in the diagnostic criteria for perinatal depression as compared to the DSM-IV; “perinatal”, as opposed to “postpartum”, is a specifier for depression with a requirement that the depression onset occurs during pregnancy or the first 4 weeks postpartum. Advances in the treatment of perinatal depression have been made over the last 3 years, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
102
0
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(115 citation statements)
references
References 76 publications
1
102
0
12
Order By: Relevance
“…PPD is a common and serious mental health problem, and one that is a source of suffering for both the mother and her offspring. It is often defined as an episode of a major or sometimes minor depressive disorder that occurs anytime within the first year postpartum [6]; however, most episodes begin within two to three months after giving birth [5,7]. The prevalence of PPD has been estimated to range from 9% to 19% depending on the recognition criteria, the period of time under consideration and population type [8].…”
Section: Introductionmentioning
confidence: 99%
“…PPD is a common and serious mental health problem, and one that is a source of suffering for both the mother and her offspring. It is often defined as an episode of a major or sometimes minor depressive disorder that occurs anytime within the first year postpartum [6]; however, most episodes begin within two to three months after giving birth [5,7]. The prevalence of PPD has been estimated to range from 9% to 19% depending on the recognition criteria, the period of time under consideration and population type [8].…”
Section: Introductionmentioning
confidence: 99%
“…American Psychiatric Association's Diagnostic and Statistical Manual of Mental Disorders, fifth edition (DSM‐5) defines PPD as a major depressive episode “with peri partum onset of mood symptoms which occur during pregnancy or within 4 weeks following delivery” (American Psychiatric, American Psychiatric Association, & American Psychiatric, ). However, although the influence of biological factors on mood 4 weeks postpartum will be significantly reduced, it is considered that the psychosocial stress that women facing during postpartum will not be relieved within 4 weeks, and the depression that occurs outside this period still produces negative outcomes and requires treatment (Stuart‐Parrigon & Stuart, ). Therefore, in the current academic study on PPD, the period is generally defined as antenatal and postnatal within one year after childbirth (O'Hara & Wisner, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, although the influence of biological factors on mood 4 weeks postpartum will be significantly reduced, it is considered that the psychosocial stress that women facing during postpartum will not be relieved within 4 weeks, and the depression that occurs outside this period still produces negative outcomes and requires treatment (Stuart-Parrigon & Stuart, 2014). Therefore, in the current academic study on PPD, the period is generally defined as antenatal and postnatal within one year after childbirth (O'Hara & Wisner, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the positive effects of fetal echocardiography, many studies have shown that suspicion of a heart malformation in the fetus leads to psychological stress during pregnancy and anxiety often accompanies the period of diagnosis. [4][5][6][7] The effects of prenatal depression and anxiety on a fetus have been researched for decades and several studies have confirmed that infants of prenatally depressed mothers are at risk of a wide variety of negative outcomes. [8][9][10][11] Fetal echocardiography is no longer limited to providing an accurate diagnosis and prognosis of CHDs and presenting various therapeutic options to the parents.…”
Section: Introductionmentioning
confidence: 99%